Observation of sagittal X‐ray diffraction by surface acoustic waves in Bragg geometry. Issue 2 (24th March 2017) - Vadilonga, Simone; Zizak, Ivo; Roshchupkin, Dmitry; Evgenii, Emelin; Petsiuk, Andrei; Leitenberger, Wolfram; Erko, Alexei
Abstract : X‐ray Bragg diffraction in sagittal geometry on a Y‐cut langasite crystal (La3 Ga5 SiO14 ) modulated by Λ = 3 µm Rayleigh surface acoustic waves was studied at the BESSY II synchrotron radiation facility. The surface acoustic waves create a dynamical diffraction grating on the crystal surface, which can be used for space–time modulation of an X‐ray beam. Abstract : X‐ray Bragg diffraction in sagittal geometry on a Y‐cut langasite crystal (La3 Ga5 SiO14 ) modulated by Λ = 3 µm Rayleigh surface acoustic waves was studied at the BESSY II synchrotron radiation facility. Owing to the crystal lattice modulation by the surface acoustic wave diffraction, satellites appear. Their intensity and angular separation depend on the amplitude and wavelength of the ultrasonic superlattice. Experimental results are compared with the corresponding theoretical model that exploits the kinematical diffraction theory. This experiment shows that the propagation of the surface acoustic waves creates a dynamical diffraction grating on the crystal surface, and this can be used for space–time modulation of an X‐ray beam.